Safranal Prevents Liver Cancer Through Inhibiting Oxidative Stress and Alleviating Inflammation - Abdalla, Youssef; Abdalla, Ali; Hamza, Alaaeldin Ahmed; Amin, Amr (Frontiers in Pharmacology, 2022)
Despite all efforts, an effective and safe treatment for liver cancer remains elusive. Natural products and their derived biomolecules are potential resources to mine for novel anti-cancer drugs. Chemopreventive effects of safranal, a major bioactive ingredient of the golden spice “saffron”, were evaluated in this study against diethylnitrosamine DEN induced liver cancer in rats. Safranal’s mechanisms of action were also investigated in the human liver cancer line “HepG2”. When administered to DEN-treated rats, safranal significantly inhibited proliferation (Ki-67) and also induced apoptosis (TUNEL and M30 Cytodeath). It also exhibited anti-inflammatory properties where inflammatory markers such as NF-kB, COX2, iNOS, TNF-alpha and its receptor were significantly inhibited. Safranal’s in vivo effects were further supported in HepG2 cells where apoptosis was induced and inflammation was down regulated. In summary, safranal is reported here as a potent chemopreventive agent against hepatocellular carcinoma (HCC) that may soon be an important ingredient of a broad-spectrum cancer therapy.